En hetero på laget - Heidi Eng (The Royal Danish Library, 2009)
A straight guy on the team.‘Raballder' is a Norwegian gay handball team competing in the mainstream national handball league. As a team they have a political consciousness towards contributing in making a difference being the only gay team in a ‘straight' handball environment in Norway. The article discuss the team's potentiality to queer up the handball arena, looking at two elements in particular that emerged during the competition season 2006/2007: 1) a straight guy enters as a player on the gay team, and becomes a figure in queering the mainstream handball context, 2) An internal conflict emerges in the team concerning the players enacting as heteronormative macho sportsmen versus as effeminate gay ‘queens' on the handball field. The latter is recognizable as gay culture which seems in this Norwegian sports context to have a deconstructive potential on male heteronormative, competitive sport.